Pedicled Descending Branch Latissimus Dorsi Mini-flap for Repairing Partial Mastectomy Defect: A New Technique. Issue 3 (March 2018) - Cai, Ruizhao; Xie, Zeming; Zhou, Lihuan; Wang, Jin; Li, Xing; Huang, Junhao; Wang, Yan; Yang, Mingtian; Chang, Edward I.; Tang, Jun
Abstract : Summary: Volume loss is 1 of the major factors influencing cosmetic outcomes of breast after partial mastectomy (PM), especially for smaller breasts, and therefore, volume replacement is critical for optimizing the final aesthetic outcome. We present a novel technique of raising a pedicled descending branch latissimus dorsi (LD) mini-flap for reconstruction of PM defects via an axillary incision. After PM, the LD mini-flap is harvested through the existing axillary incision of the axillary dissection or the sentinel lymph node biopsy. The descending branches of thoracodorsal vessels and nerve are carefully identified and isolated. The transverse branches are protected to maintain muscle innervation and function. The LD muscle is then undermined posteriorly and inferiorly to create a submuscular pocket and a subcutaneous pocket between LD muscle and superficial fascia. Once the submuscular plane is created, the muscle is divided along the muscle fibers from the deep surface including a layer of fat above the muscle. Finally, the LD mini-flap is transferred to the breast defect. Given the limited length and mobility of the LD mini-flap, this approach is best utilized for lateral breast defects. However, for medial defects, the lateral breast tissue is rearranged to reconstruct the medial breast defect, and an LD mini-flap is then used to reconstruct the lateral breast donor site. This technique can therefore be employed to reconstruct all quadrants of the breast and can provide aesthetic outcomes without scars on the back, with minimal dysfunction of LD muscle. Abstract : Supplemental Digital Content is available in the text.